Improved stability and tumor targeting of 5‐fluorouracil by conjugation with hyaluronan. Issue 2 (11th April 2013) - Dong, Zhikui; Zheng, Wenyi; Xu, Zaiyang; Yin, Zongning
<x xml:space="preserve">Abstract</x> To circumvent the rapid clearance in vivo and consequent low tumor targeting of 5‐fluorouracil (5‐Fu), hyaluronan‐5‐fluorouracil conjugate (HA‐5‐Fu) was firstly synthesized and characterized. The stability of HA‐5‐Fu in vitro was evaluated by incubation with phosphate buffered saline, hyaluronidase solution, and mice plasma, respectively. The tumor targeting was tested by in vitro cytotoxicity evaluation and in vivo pharmacokinetics study in plasma and tumor. HA‐5‐Fu with drug loading of 87.674 mg/g was successfully obtained and confirmed. HA‐5‐Fu showed high stability in acidic environment and moderate stability under enzymatic cleavage. The enhanced cytotoxicity of HA‐5‐Fu over 5‐Fu depended on drug concentration, incubation time, and cell lines type. The t1/2 of HA‐5‐Fu in plasma after injection of prodrug was extended up to 10 times compared with that of 5‐Fu. Notably, AUC0–t in tumors of HA‐5‐Fu was 3.6 times higher than 5‐Fu, demonstrating its excellent tumor targeting and quite promising prospect in anti‐cancer therapy. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 927‐932, 2013